ASSESSMENT OF ATOPIC DERMATITIS IMPACT ON A QUALITY OF LIFE OF A SICK CHILD'S FAMILY - L.S. Namazova-Baranova; N.G. Korotkiy; G.A. Novik; F.I. Petrovskii; V.V. Pyzh; R.M. Torshkhoeva; A.A. Tikhomirov; T.S. Likhacheva; S.Sh. Gasymova; A.A. Uliyanov (Union of pediatricians of Russia, 2010)
The authors have conducted a study with the aim of evaluating the internal reliability of the developed questionnaire to determine the impact of atopic dermatitis on the life of a sick child's family, examining the interrelationship of its parameters with pharmacotherapy and intensity of disease presentation before and during treatment. It was found that internal reliability is medium. The questionnaire's values proved dependent on the intensity of manifestations (objective SCORAD), outcomes (objective SCORAD after treatment) and after-effects (adverse events) of therapy, as well as on the age and duration of disease. Key words: atopic dermatitis, a questionnaire to determine the impact of atopic dermatitis on the life of a sick child's family. (Pediatric Pharmacology. - 2010; 7(4):62-67)